Comparison of Serial and Parallel Connections of Membrane Lungs against Refractory Hypoxemia in a Mock Circuit - Albert J. Omlor; Stefan Caspari; Leonie S. Omlor; Anna M. Jungmann; Marcin Krawczyk; Nicole Schmoll; Sebastian Mang; Frederik Seiler; Ralf M. Muellenbach; Robert Bals; Philipp M. Lepper (Membranes, 2023)
Extracorporeal membrane oxygenation (ECMO) is an important rescue therapy method for the treatment of severe hypoxic lung injury. In some cases, oxygen saturation and oxygen partial pressure in the arterial blood are low despite ECMO therapy. There are case reports in which patients with such instances of refractory hypoxemia received a second membrane lung, either in series or in parallel, to overcome the hypoxemia. It remains unclear whether the parallel or serial connection is more effective. Therefore, we used an improved version of our full-flow ECMO mock circuit to test this. The measurements were performed under conditions in which the membrane lungs were unable to completely oxygenate the blood. As a result, only the photometric pre- and post-oxygenator saturations, blood flow and hemoglobin concentration were required for the calculation of oxygen transfer rates. The results showed that for a pre-oxygenator saturation of 45% and a total blood flow of 10 L/min, the serial connection of two identical 5 L rated oxygenators is 17% more effective in terms of oxygen transfer than the parallel connection. Although the idea of using a second membrane lung if refractory hypoxia occurs is intriguing from a physiological point of view, due to the invasiveness of the solution, further investigations are needed before this should be used in a wider clinical setting.